ANALISIS PENERAPAN PEMBELAJARAN BERDIFERENSIASI DALAM KURIKULUM MERDEKA PADA MATERI TATA SURYA DI KELAS VII SMP - Devi Kurnia Fitra (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2022)
The implementaton of differentiated learning in the Independent Curriculum on the Solar System material in class VII SMP Negeri 1 Tembilahan is a Classroom Action Research conducted in two cycles to improve learning and student activity. Starting with a diagnostic assessment, the teacher can carry out learning according to the learning needs of students. From the results obtained a significant increase in student learning outcomes from the pre-cycle, cycle I and cycle II. Thus, differentiated learning is one of the definite learning approaches to the independent curicculum.